Multiple centre evaluation study of ADAMTS13 activity and inhibitor assays. (6th November 2017) - Langley, K.; Fretwell, R.; Kitchen, S.; MacDonald, S.; Dutt, T.; Baker, P.; Singh, D.; McDonald, V.; Hughes, C.; Murphy, P.; Scully, M.
Abstract: Introduction: Accurate evaluation of ADAMTS13 activity is required for the diagnosis and clinical management of thrombotic microangiopathies, and commercial kits are available for routine laboratory use. Methods: Our study compares the results from Technoclone (Technoclone GmbH, Austria) activity and Inhibitor kits with specialist laboratory reference methods (FRETS and ELISA IgG) and the impact of transporting frozen samples and comparison of results. Results: This multicentre study identified differences in Technoclone activity results compared to specialist testing, which could potentially impact diagnosis. A change in the commercial kit during the study period appears to have rectified the detection levels. Frozen samples provided comparable results between sites. Conclusion: With close attention to normal ranges, commercial kits are suitable for use in the clinical diagnosis of thrombotic microangiopathies and frozen transportation of samples between sites is a suitable approach. However, a robust external quality control system is essential to provide an independent evaluation of changes in kit production.